To be a woman here is to be invisible: in search of the dispossessed femininity in Middle-earth - Jansson, Pirita (My University, 2016)
In my thesis I examine J.R.R. Tolkien’s The Lord of the Rings (1954-55), the fantasy epic written on the basis of a fictional universe created by Tolkien, complete with elves, dwarves and other mystical creatures – with languages, alphabets and grammar created for all. While rich linguistically, Tolkien writes a decidedly male description of his world, often neglecting any acknowledgement of female existence. Tolkien’s monolithic stature amongst other fantasy authors made me conduct a feminist reading of The Lord of the Rings, with an eye for the way female experience is marginalized to the point of omission. Tolkien’s linguistic accomplishments have overshadowed the illogical aspects of his work, namely the omission of genders, societal classes and features of society necessary for the fictional universe to retain its cohesion. This cohesion suffers from a totally male experience in the novel which is willfully blind to these features I listed. My theoretical framework is built on ideas in Toril Moi’s Sex, Gender and the Body (2005) and bell hook’s Feminism is For Everybody (2000). Michel Foucault’s ideas of power and hidden histories assist in performing a close reading of the source text and interpreting the results. My thesis focuses on the transformation that the values associated with the concept of equality have undergone. This is best illustrated in the treatment of the few female characters in the novel – Galadriel, Éowyn and Arwen – as their beauty and existence interferes with the ordering of the male-dominated world.